Edutheology as an Idea for Revitalizing Education in Indonesia - Asep Syahrul Mubarok; Hasbullah Hasbullah; Repa Hudan Lisalam; Saefudin Zuhri (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
Indonesian education is facing various challenges related to the integrity, morality, and intellectual quality of students. This condition indicates the need to strengthen the foundation of values in the education system. This article aims to examine the educational values contained in QS. Al-'Alaq verses 1-5 and their relevance as an idea for revitalizing education in Indonesia through the concept of Edutheology. This research uses a library research method with a normative, historical, and sociocultural approach. The analysis is carried out through an interpretive study of QS. Al-'Alaq verses 1-5 which is then connected to the historical context of Indonesian society and contemporary educational challenges. The results of the study indicate that the concept of iqra' in the verse not only represents intellectual activity but also contains a theological dimension that positions the learning process as a manifestation of monotheistic awareness. This concept encourages humans to read and understand various realities comprehensively. This conceptual finding leads to the idea of monotheism-based education (Edutheology) as a framework for educational revitalization that integrates scientific and spiritual dimensions so that it can encourage the realization of a more civilized and progressive Indonesian educational climate.